Sorption of Metal Ions from Aqueous Solutions by Humic Substances - Ismagilov, Z. R.; Smirnov, V. G.; Malyshenko, N. V.; Zherebtsov, S. I. (Solid fuel chemistry, 2023)
Humic substances (HSs) extracted from brown coal, peat, and other sources are considered as an efficient and affordable sorbent used to trap and bind heavy metal ions, which are hazardous to the environment. This paper provides an overview of modern works on this subject matter. Typical structural characteristics and properties of HSs and methods for their extraction from brown coal, peat, swamp waters, and other media are described, and quantitative results of a wide range of experiments on the sorption of metal ions by HSs are presented. Significant fluctuations in the measured sorption capacity of HSs in different experiments probably arise not so much due to variations in the elemental composition and structure of HSs extracted from different sources, but they are associated with experimental conditions, such as the acidity (pH) of solution, ionic strength, concentration of metal ions, and concentration of HSs in the solution. In terms of the order of magnitude, the maximum sorption capacity of HSs is comparable to the total concentration of surface carboxyl and hydroxyl groups, and it amounts to several millimoles of metal ions per gram of HSs.